Distally edentulous maxillary left-sided arch with pneumatized sinus area restored with corticobasal implants - A case report - Senthilnathan Radhakrishnan (Wolters Kluwer Medknow Publications, 2021)
Restoration of severely atrophied ridges with conventional implants requires extensive surgical procedures which are totally expensive, and it also involves a great deal of postoperative discomfort to a patient. In such situations, basal implants come to rescue for rehabilitation where it utilizes the cortical bone for anchorage. The availability of several designs of these implants that exist today has made basal implantology flexible enough to accommodate any situation. This article is a case report of the patient whose maxillary arch was fully rehabilitated with endodontically treated teeth and fixed partial denture. The remaining edentulous region in the maxillary left side was treated with corticobasal implants and was rehabilitated with a fixed PFM prosthesis. The above-mentioned case has a follow-up of 3 years, and still, the implant-supported prosthesis provides better function for the patient.